LINGUISTIC ASPECTS OF THE USE OF HUMOROUS CONTENT MATERIALS AND THEIR FEATURES IN TEACHING ENGLISH (World Bulletin of Education and Learning, 2026)
Humor is a personal realization of the comic book category, which is an aesthetic and philosophical category denoting culturally conceived, socially and aesthetically significant laughter, and from the point of view of communicative linguistics, humor is a social phenomenon that occurs in a certain context and includes features of the national and regional language, as well as related to various cultural and cultural aspects. social factors.
Keywords: Linguistics, culture, history, linguacultural, comparison, intertextuality, stereotype.